From Embryo to Adult: Low Temperatures Affect Phase Transitions of Allium sativum L. from Germination to Flowering - Tomer E. Ben Michael; Liraz Rozenblat; Adi Faigenboim; Einat Shemesh-Mayer; Itzhak Forer; Ross Peters; Joshua D. Klein; Haim D. Rabinowitch; Rina Kamenetsky Goldstein (Agronomy, 2020)
Juvenile and vegetative adult shoot apical meristems (SAM) are actively involved in acquisition of flowering competence, while the embryonic SAM is regarded as “responsible” only for germination. Comparative analyses of imbibed and stratified seeds of garlic Allium sativum show that only stratified seedlings produced bulbs and flower stems at the end of the season. Since the seed morphology of stratified and non-stratified seeds prior to sowing was similar, the differences are attributed to the molecular alterations in the embryonic SAM. Functional annotation analysis of 3000 differentially expressed genes suggests that seed imbibition reactivates the embryonic cell cycle, initiates the metabolism, and primes garlic seed germination. Stratification enhances DNA modifications, biosynthesis, cellular transport, and tissue development. Similar to vernalization of the vegetative buds, stratification of the embryonic SAM resulted in altered expression of meristem-identity and flowering homologs. Phase transitions from seed germination to flowering and bulbing in A. sativum are tightly connected, and possibly associated with downregulation of specific flowering repressor(s). The embryonic SAM plays an important role not only in seed germination, but in the entire plant life cycle, providing the foundation for the genetic regulation of major functional shifts in metabolism and development.